The Effect of Time on Holding the Peace - Abd , Tariq; Hamad, Youssef (Islamic Sciences Journal, 2023)
ABSTRACT Time is an influencing factor on contracts, through its impact on the pillars of the contract, its conditions, and its effects. This research paper is concerned with studying the impact of time on the peace contract, especially that the term is of great importance in the stability and demise of the contract, by specifying the time of delivery, and specifying the time of arrest, the contracting parties’ agreement on installments and the exchange by astrology, and other conditions and elements that are not free of time. Therefore time is the most prominent factor in the peace contract, and this is what makes it a cause for disagreement and a source of disagreement between the two contracting parties, hence the importance of research in this topic.